Sociobiology meets oncology: unraveling altruistic cooperation in cancer cells and its implications - Muhammad Sufyan bin Masroni; Evelyn Siew-Chuan Koay; Victor Kwan Min Lee; Siok Bian Ng; Soo Yong Tan; Karen Meiling Tan; Marco Archetti; Sai Mun Leong (Experimental and Molecular Medicine)
Abstract Altruism, an act of benefiting others at a cost to the self, challenges our understanding of evolution. This Perspective delves into the importance of altruism in cancer cells and its implications for therapy. Against the backdrop of existing knowledge on various social organisms found in nature, we explore the mechanisms underlying the manifestation of altruism within breast tumors, revealing a complex interplay of seemingly counteracting cancer signaling pathways and processes that orchestrate the delicate balance between cost and benefit underlying altruistic cooperation. We also discuss how evolutionary game theory, coupled with contemporary molecular tools, may shed light on understudied mechanisms governing the dynamics of altruistic cooperation in cancer cells. Finally, we discuss how molecular insights gleaned from these mechanistic dissections may fuel advancements in our comprehension of altruism among cancer cells, with implications across multiple disciplines, offering innovative prospects for therapeutic strategies, molecular discoveries, and evolutionary investigations.